Pengembangan Video Pembelajaran IPA Berbasis Doratoon dengan Model ADDIE bagi Siswa SMP - Nurwahyuni Mansyur; Syamsunir; Muhammad Takdir; Handy Ferdiansyah (Science and Education Journal (SICEDU), 2026)
This study aims to produce a valid and practical Doratoon web-based science learning video media for eighth grade students at UPT SMP Negeri 2 Kulo. The background of this study is the low visualization of abstract science concepts, so it requires innovative media to help students' understanding. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. Data collection instruments include validation sheets for material experts and media experts, as well as response questionnaires for teachers and students to measure practicality. The results of the study showed that the Doratoon learning video media was declared "Very Valid" by material experts with a score of 92% and media experts with a score of 88%. The results of the practicality test by teachers obtained 90% results and 92% of students also showed the "Very Practical" category. Thus, this Doratoon-based learning video media is valid and practical to be used as a supporting tool for science learning to visualize complex concepts in an interesting and interactive manner.